Steven Universe art & origins - McDonnell, Chris (Christopher) 1979- (Abrams, 2017)
Steven Universe: Art & Origins is the first book to take fans behind the scenes of the groundbreaking and boundlessly creative Cartoon Network animated series Steven Universe. The eponymous Steven is a boy who--alongside his mentors, the Crystal Gems (Garnet, Amethyst, and Pearl)--must learn to use his inherited powers to protect his home, Beach City, from the forces of evil. Bursting with concept art, production samples, early sketches, storyboards, and exclusive commentary, this lavishly illustrated companion book offers a meticulous written and visual history of the show, as well as an all-access tour of the creative team's process. Steven Universe: Art & Origins reveals how creator Rebecca Sugar, the writers, the animators, and the voice actors work in tandem to bring this adventure-packed television series to life.